Comment on "Perturbation Analysis of the Nonlinear Matrix Equation X-∑i=1mAi*XpiAi=Q". (9th October 2013) - Berzig, Maher; Karapınar, Erdal
Abstract : We show that the perturbation estimate for the matrix equation X - ∑ i = 1 m A i * X p i A i = Q due to J. Li, is wrong. Our discussion is supported by a counterexample.